2013
DOI: 10.1158/2159-8290.cd-12-0049
|View full text |Cite
|
Sign up to set email alerts
|

Loss of 53BP1 Causes PARP Inhibitor Resistance in Brca1-Mutated Mouse Mammary Tumors

Abstract: Inhibition of PARP is a promising therapeutic strategy for homologous recombinationdefi cient tumors, such as BRCA1-associated cancers. We previously reported that BRCA1-defi cient mouse mammary tumors may acquire resistance to the clinical PARP inhibitor (PARPi) olaparib through activation of the P-glycoprotein drug effl ux transporter. Here, we show that tumorspecifi c genetic inactivation of P-glycoprotein increases the long-term response of BRCA1-defi cient mouse mammary tumors to olaparib, but these tumor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
415
2
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 451 publications
(441 citation statements)
references
References 38 publications
20
415
2
4
Order By: Relevance
“…Next, we determined the response of KB1P-MET carcinosarcomas to AZD2461, a PARP inhibitor with strongly reduced affinity to Pgp (28). KB1P-MET carcinosarcomas with high Pgp expression (donors 1 and 2) responded well to AZD2461, confirming Pgp-mediated resistance to olaparib (Fig.…”
Section: Increased Pgp Expression In Kb1p-met Carcinosarcomas Causesmentioning
confidence: 79%
See 1 more Smart Citation
“…Next, we determined the response of KB1P-MET carcinosarcomas to AZD2461, a PARP inhibitor with strongly reduced affinity to Pgp (28). KB1P-MET carcinosarcomas with high Pgp expression (donors 1 and 2) responded well to AZD2461, confirming Pgp-mediated resistance to olaparib (Fig.…”
Section: Increased Pgp Expression In Kb1p-met Carcinosarcomas Causesmentioning
confidence: 79%
“…We have previously shown that restoration of HR by somatic mutation of Trp53bp1 encoding 53BP1 occurs in 25% of KB1P mammary tumors with acquired resistance to AZD2461 (28). Whether reduced 53BP1 expression in the AZD2461-resistant KB1P-MET carcinosarcoma is a consequence of MET-induced EMT or caused by (epi)genetic alterations of Trp53bp1 remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of BRCA1 or with enhanced retention of 53BP1 at DSB sites, cells primarily use the error-prone NHEJ to repair DSBs throughout the cell cycle, which leads to gene rearrangement, cell death, and increased sensitivity to anticancer therapies (9-11). Consistently, BRCA1-null mice are early embryonic lethal (12, 13) and codepletion of TP53BP1 rescued the lethality phenotype of BRCA1-null mice (12)(13)(14).Low expression level of 53BP1 was found to be associated with poor clinical outcome in triple negative breast cancer patients with BRCA1 mutation (12, 15), as well as resistance to genotoxins and poly(ADP-ribose) polymerase inhibitors (12,16,17). This finding is probably because loss of 53BP1 restored HR and promoted cell survival (12-14).…”
mentioning
confidence: 93%
“…Low expression level of 53BP1 was found to be associated with poor clinical outcome in triple negative breast cancer patients with BRCA1 mutation (12, 15), as well as resistance to genotoxins and poly(ADP-ribose) polymerase inhibitors (12,16,17). This finding is probably because loss of 53BP1 restored HR and promoted cell survival (12-14).…”
mentioning
confidence: 99%
“…Loss of 53BP1 allowed end resection of breaks ends, which is an important step in preparing the DNA strand for HR rather than NHEJ (13,22,23) This partial restoration rendered tumor cells more resistant to cisplatin, mitomycin C, and olaparib (a PARP inhibitor; refs. 13,24). Subsequently, 53BP1 expression was investigated in two cohorts of patients.…”
Section: Introductionmentioning
confidence: 99%